Idiopathic Thrombocytopenic Purpura in Patients with Ischaemic Heart Disease - A Therapeutic Challenge - Islam, AKM Monwarul; Ahmed, Tanveer; Shimu, Ishrat Jahan; Nahar, Samsun; Rahman, Mohammad Arifur; Rahman, Afzalur (Bangladesh Heart Journal, 2018)
Idiopathic thrombocytopenic purpura (ITP) and myocardial infarction (MI) in an individual patient is a rare combination. MI mandates thrombolytic and antiplatelet therapy which increases the risk of bleeding in ITP. So far, no guideline deals with management protocol for ischaemic heart disease (IHD) in ITP patients. Here, we describe 2 cases of IHD who developed ITP while on antiplatelet therapy. Bangladesh Heart Journal 2018; 33(1) : 74-77